2020
DOI: 10.3389/fphar.2020.577571
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Macrophages as a Therapeutic Option in Coronavirus Disease 2019

Abstract: Immune cells of the monocyte/macrophage lineage are characterized by their diversity, plasticity, and variety of functions. Among them, macrophages play a central role in antiviral responses, tissue repair, and fibrosis. Macrophages can be reprogrammed by environmental cues, thus changing their phenotype during an antiviral immune response as the viral infection progresses. While M1-like macrophages are essential for the initial inflammatory responses, M2-like macrophages are critical for tissue repair after p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 167 publications
(216 reference statements)
4
39
0
Order By: Relevance
“…This supports the efficacy of tocilizumab (IL-6 receptor inhibitor) in severe disease (Horby et al, 2021b), moreover we find upregulation of IL6R in more severe disease. Our data supports the use of inhibitors of GM-CSF in current clinical trials, use of anti-CCL2 (Gracia-Hernandez et al, 2020), repurposing of immune checkpoint inhibitors (Pezeshki and Rezaei, 2021) to restore/enhance CD8 + T cell cytotoxicity, and potential targets such as FGFRs, which are cofactors for early stage viral infection upregulated by MERS-CoV2 leading to lung damage and proposed as a therapeutic target (Hondermarck et al, 2020).…”
Section: Discussionsupporting
confidence: 75%
“…This supports the efficacy of tocilizumab (IL-6 receptor inhibitor) in severe disease (Horby et al, 2021b), moreover we find upregulation of IL6R in more severe disease. Our data supports the use of inhibitors of GM-CSF in current clinical trials, use of anti-CCL2 (Gracia-Hernandez et al, 2020), repurposing of immune checkpoint inhibitors (Pezeshki and Rezaei, 2021) to restore/enhance CD8 + T cell cytotoxicity, and potential targets such as FGFRs, which are cofactors for early stage viral infection upregulated by MERS-CoV2 leading to lung damage and proposed as a therapeutic target (Hondermarck et al, 2020).…”
Section: Discussionsupporting
confidence: 75%
“…These results suggest that macrophages-derived pro-inflammatory cytokines play an essential role in cytokine storms, and thus these molecules are thought to be associated with COVID-19-associated ARDS mortality [ 66 ]. To ameliorate the complications induced by cytokine storms, targeting IL-6 studies are currently being conducted [ 67 , 68 , 69 ]. Researchers have reported that the MAPK pathway is well recognized in viral infection [ 70 ].…”
Section: Macrophages In Covid-19-related Ardsmentioning
confidence: 99%
“…Pulmonary fibrosis, along with cytokine storms, accompany SARS-CoV-2 [ 67 ]. M2-type macrophages are thought to play an important role in the fibrosis of COVID-19.…”
Section: Macrophages In Covid-19-related Ardsmentioning
confidence: 99%
“…In addition, anti-IL-6 chimeric monoclonal antibodies, Siltuximab, are also given, which directly blocks the IL-6-associated inflammation, and thereby, these drugs improve the clinical outcome by controlling the body temperature together with improved peripheral oxygen saturation and minimized the inflammatory storm [ 269 ]. Moreover, there are several ongoing trials for COVID-19 patients to target the macrophage activation to reduce the hyper inflammation state inside the patients, where the drugs are targeted against other pro-inflammatory cytokines and chemokine such as IL-1ß, TNF-α, IFN-γ and CCR5 [ 270 ]. COVID-19 patients exhibiting hypoxemia are addressed with the supplemental oxygen support as an initial step during the hospitalization, though the type of support depends on the reported oxygen saturation [ 271 ].…”
Section: Possible Therapeutic Approaches Against Sars-cov-2 Induced Complicationsmentioning
confidence: 99%